(untitled) (Research, Society and Development, 2022)
Post-dural puncture headache (PDH) is the most frequent complication of subarachnoid anesthesia, with an incidence ranging from 0.04 to 3%. It usually appears within seven days after a dural puncture, lasting approximately two weeks and is usually self-healing. During the period of pain, the patient may have his daily routine impaired, as the condition typically worsens when the orthostatic position is adopted. Several risk factors can contribute to the appearance of the complication, and they can be related to the patient, the puncture technique and the material used. The diagnosis of PDH is clinical, and the therapeutic approach varies according to the presentation and severity of the pain, and may be clinical or, ideally, epidural blood patch. The objective of this study was to identify the frequency of PDH treated with blood patch, associated with clinical and sociodemographic factors in a hospital in the city of Três Lagoas/MS. This is a descriptive, retrospective cross-sectional cohort study, via document analysis for the investigation of epidural blood patch performed from secondary headache, in patients who underwent subarachnoid anesthesia, from 01/01/2011 to 04/03/2019. 57 epidural blood buffers were identified, with a prevalence rate of 0.25%, annual fluctuating incidence and a predominance of females. Of the total, 49 (86%) were women, 36 (63%) patients were between 21 and 40 years old and 52 (91%) of them had PDH symptoms within 5 days post-anesthesia. It can be concluded that epidural blood packing for the treatment of PDH is still common and without definitive resolution. The need for constant adoption of evident prophylactic measures that can reduce the incidence of the complication is absolute, since the patient’s return to the operating room is accompanied by infectious, psychosocial and socioeconomic impacts.